EXAMINING OCCUPATIONAL ANXIETY LEVELS OF PHYSICAL EDUCATION AND SPORTS TEACHER DEPARTMENT STUDENTS - ÖZBAL, Ayşe Feray; EKTİRİCİ, Arıkan (Sportif Bakış: Spor ve Eğitim Bilimleri Dergisi, 2017)
The aim of this study was to examine the occupational anxiety levels of physical education and sports teacher department students in terms of age, gender, university, grade level, mother’s and father’s educational levels and family income. A total of 511 students (208 female, 303 male) from 6 different universities participated in the study. Independent samples t-test for gender and age variables; One-way Analysis of Variance (ANOVA) was used for grade level, university, mother’s and father’s education levels and family income. Significant differences were found in Interaction With Students, Occupational Exam subscales in terms of gender; Interaction With Students and Individual Self-Development subscales in terms of age (p<.05). There was no significant difference according to university, mother’s and father’s education levels and family income variables (p>.05). As a result, It can be concluded that the significant difference between gender groups is derived from social values, and the difference in age groups is due to lack of occupational qualification.